Japan's Cultural Diplomacy Through Anime and Manga in Promoting the 2020 Tokyo Olympics - Kurnia Handoyo, Fajar (Pelopor Publikasi Akademika, 2024)
The objectives of this study are to japan's cultural diplomacy through anime and manga in promoting the 2020 tokyo olympics. With the pandemic arising on the horizon, Tokyo 2020’s Olympics had to suffer schedule setbacks for almost a year, amongst many other causalities from its wake. The practice of cultural diplomacy is a legitimized act of soft power move by one’s countries upon others. In the modern age comes with details of many mediums and types that enhance the mainlined diplomacy acts. Japan’s usage of anime and manga culture had taken over the world by storm along with its fans that are interconnecting the further attempt at mutual understanding, and universally shared values. By using nine characters from beloved manga and promoting the Olympics through cooperation with famed anime studios, the result is a magnanimous and harmonious symbiotic relationship that blooms within international sportsmanship. The Covid-19 pandemic has forced this development to direct humanity to places that perhaps 15 years ago were said to be almost impossible, including reduced space for face-to-face meetings, restrictive regulations, and also sanctions that must be implemented regarding matters around related topics.